The Infectious Disease Diagnosis A Case Approach (Springer International Publishing, 2018)
This text uses cases to illustrate differential diagnoses of various infectious diseases. Unlike any other book on the market, this book is specifically designed for ease of use and can cater to a variety of medical professionals and their needs. The text features brief cases that allow for quick readability, an appendix particularly designed for cross-referencing cases with common symptoms, exposures, and putative diagnoses, bulleted conclusion points, and differential diagnoses tables. Each case is written by an expert in the field and includes a discussion that leads the reader through the logical process of deduction to narrow the diagnosis as well as the laboratory testing, physical examination findings, and elements of the patient's history and exposures utilized to make a diagnosis. Chapters conclude with a focused review on a specific topic related to diagnosis, treatment, or prognosis that the case illustrates, including references for further reading on the topics from the literature. The Infectious Disease Diagnosis is an outstanding resource for infectious disease specialists, internal medicine physicians, emergency room staff, primary care and general practice physicians, family practitioners, consultants in infectious disease, medical students, residents, fellows, and trainees who diagnose patients.